Weeping and smiling in Dante's works - Bonaldi, Giulia (Trinity College Dublin. School of Lang, Lit. & Cultural Studies. Discipline of Italian, 2022)
This study shows the function and significance of tears and smiles in two of Dante's major works, the Vita Nuova and the Commedia, filling a lacuna in the existing literature: this dissertation constitutes the first comprehensive work that analyses the representation of the two emotional expressions in Dante's writing. Focusing on their literary representation and their role within the author's theological thought, this study shows how the binary emotional system of weeping and smiling contributes to regulate and shape the structure of Dante's works, revealing their theological and poetic foundations and tracing the author's contribution to the conception of smiling and weeping in the Middle Ages. Concerning weeping, I show that the representation of tears in the Vita Nuova marks the gradual passage from Dante's total adherence to the tradition of love poetry to his detachment from it, through the conversion of tears from a manifestation of lovesickness to a fundamental penitential tool for Christian salvation. This process reaches its fulfilment in the Commedia, where tears play a central role in Dante's journey of expiation, corresponding to a biblical progression from tears to smiles - from sin to bliss - which defines the structure of the poem itself. As for the Inferno, my study observes Dante's reappropriation of earlier literary and theological concepts to create a primary poetic representation of infernal weeping, both in extent and value, through the representation of tears as the main instrument of divine punishment. Moreover, this dissertation underscores the role of salvific tears in Dante's groundbreaking definition of Purgatory, both as an intermediary kingdom between Hell and Paradise and the celebration of a new sensibility, of an interior communication with God that must always pass through tears. Regarding smiles, I demonstrated how Dante creates the first literary codification of the category of the smile in Italian literature, resolving the problematic nature of laughter in an expression that openly celebrates knowledge and divine love. I identify the first stage of this process in Beatrice's first smile in the Vita Nuova, which transforms the traditional laughter of the courtly lady into a smile that reveals the miraculous nature of woman. In terms of the Commedia, I show how Dante accomplishes the creation of an afterlife structured around the smile as a reward of beatitude, observing the gradual transformation of the smile from an expression of wisdom in Purgatorio into the primary manifestation of the divine within the human in Paradiso. Indeed, this study suggests that Dante develops a theology of the smile representing its progressive divinization, which can be observed first through the mediation of Beatrice's and the Virgin's smiles, and then in the extraordinary depiction of the smile of God concluding the third canticle, which provides an image of Creation as a smile.
APPROVED
Keywords: Smiling; weeping; Dante Alighieri; History of emotions; Italian medieval literature